Tapering for strength-power individual event and team sport athletes - Bazyler, C. (Electronic Theses and Dissertations, 3089, 2016)
The overall purpose of this dissertation was to address mechanistic and performance changes following a peaking phase in individual event and team sport strength-power athletes. This purpose was addressed by conducting 4 separate investigations with track and field athletes, volleyball athletes, and a national level weightlifter. The following are the primary findings from these investigations. Division I collegiate throwers increased competition throwing performance, jumping performance, and preserved muscle architecture characteristics following an overreach and taper. There were moderate decreases in division I female collegiate volleyball athlete`s vastus lateralis muscle thickness with no statistical changes in jumping performance following a taper with no prior overreach in. There were moderate to very large differences in countermovement jump height supercompensation during the peaking phase in favor of the returners over the new players on a similar team of female volleyball athletes. Changes in serum concentrations of inflammatory, hypertrophic and endocrine markers corresponded with alterations in training volume-load and partially explained changes in jump, dynamic mid-thigh pull, and weightlifting performance following multiple competition phases in a national level weightlifter. Additionally, vastus lateralis cross-sectional area can be maintained following a competition phase in a high level weightlifter provided large changes in body mass are not attempted close to competition. The findings of these investigations support the use of overreach and tapering for strength-power athletes and provide an underlying biochemical, morphological, and biomechanical basis for the observed changes in performance.